Mobile virtual reality to develop a virtual laboratorium for the subject of digital engineering - Mohamed Nor Azhari bin Azman (Tanjong Malim, 2019)
Mobile virtual reality to develop a virtual laboratorium for the subject of digital engineering by Mohamed Nor Azhari bin Azman